The effect of the sex of a model on nocebo hyperalgesia induced by social observational learning - SWIDER, Karolina; BABEL, Przemysław (Pain (Amsterdam), 2013)
Nocebo hyperalgesia was induced by social observational learning. Its magnitude was greater after a male rather than a female model was observed. Research shows that placebo analgesia can be induced through social observational learning. Our aim was to replicate and extend this result by studying the effect of the sex of both the model and the subject on the magnitude of placebo analgesia induced by social observational learning. Four experimental (1 through 4) and 2 control (5 and 6) groups were observed: groups 1, 3, and 5 were female; groups 2, 4, and 6 were male. All subjects received pain stimuli of the same intensity preceded by green and red lights. Before receiving pain stimuli, groups 1 and 4 observed a female model and groups 2 and 3 a male model; both models simulated responses to pain stimuli preceded by green lights as less painful than those preceded by red lights. Groups 1 through 4 also rated pain stimuli preceded by green lights as less painful. Further investigation revealed that in fact subjects in experimental groups rated red-associated stimuli as more painful than subjects from control groups who did not observe a model before receiving the same pain stimuli, indicating that nocebo hyperalgesia rather than placebo analgesia was induced. Empathy traits predicted the magnitude of nocebo hyperalgesia. Regardless of the sex of the subject, nocebo hyperalgesia was greater after the male model was observed. The results show that social observational learning is a mechanism that produces placebo effects. They also indicate that the sex of the model plays an important role in this process.